No evidence synthesis about me without me: Involving young people in the conduct and dissemination of a complex evidence synthesis - Erin Walker; Elizabeth Shaw; Michael Nunns; Darren Moore; Jo Thompson Coon (Wiley, 2021)
Abstract Objectives To describe and reflect on the methods and influence of involvement of young people with lived experience within a complex evidence synthesis. Study design and setting Linked syntheses of quantitative and qualitative systematic reviews of evidence about interventions to improve the mental health of children and young people (CYP) with long‐term physical conditions (LTCs). Methods Involvement was led by an experienced patient and public involvement in research lead. Young people with long‐term physical conditions and mental health issues were invited to join a study‐specific Children and Young People's Advisory Group (CYPAG). The CYPAG met face to face on four occasions during the project with individuals continuing to contribute to dissemination following report submission. Results Eight young people joined the CYPAG. Their views and experiences informed (a) a systematic review evaluating the effectiveness of interventions intended to improve the mental health of CYP with LTCs, (b) a systematic review exploring the experiences of interventions intended to improve the mental well‐being of CYP with LTCs and (c) an overarching synthesis. The CYPAG greatly contributed to the team's understanding and appreciation of the wider context of the research. The young people found the experience of involvement empowering and felt they would use the knowledge they had gained about the research process in the future. Conclusion Creating an environment that enabled meaningful engagement between the research team and the CYPAG had a beneficial influence on the young people themselves, as well as on the review process and the interpretation, presentation and dissemination of findings.